Feature analysis using line sweep thinning algorithm - Fu Chang; Ya-Ching Lu; Pavlidis, T. (IEEE transactions on pattern analysis and machine intelligence, 1999)
We propose a new thinning algorithm based on line sweep operation. Assuming that the contour of the figure to be thinned has been approximated by polygons, the "events" are then the vertices of the polygons, and the line sweep algorithm searches for pairs of edges lying within each slab. The pairing of edges is useful for detecting both regular and intersection regions. The regular regions can be found at the sites where pairings between edges exist. Intersection regions are those where such relations would cease to exist. A salient feature of our approach is that it finds simultaneously the set of regular regions that attach to the same intersection region. Such a set is thus called an intersection set. The output of our algorithm consists of skeletons as well as intersection sets, both can be used as features for subsequent character recognition. Moreover, the line sweep thinning algorithm is efficient in computation as compared with a pixel-based thinning algorithm which outputs skeletons only.